SUPERVISI AKADEMIK BIDANG KOMPETENSI PEDAGOGIK GURU KECAMATAN LUBUK BEGALUNG - Lathifah, Najmi Diyana (UIN Imam Bonjol Padang, 2024)
This research is motivated by the importance of implementing academic supervision to overcome the problem of lack of teacher creativity in making tools, learning media, the methods taught are not updated, teachers are less effective in implementing learning, there are teachers who are less able to prepare and develop lesson plans independently because there is a new curriculum. The research method used isqualitative with data collection techniques through observation, interviews and documentation. The data analysis technique in this research is, data collection, data reduction, data presentation, and drawing conclusions. Research Results: (1) The program for implementing academic supervision is carried out using a process, planning an academic supervision program which is designed at the beginning of each semester, implementing academic supervision which is carried out continuously, and following up on the results of academic supervision by providing training and workshops. (2) The approach to implementing academic supervision uses a direct approach (directive) by approaching the teacher and not blaming the teacher, anindirect approach (non-directive) through teacher council meetings with the school principal, a collaborative approach by conducting discussions and self-reflection. (3) Techniques for implementing academic supervision use individual techniques by conducting class visits, observation visits, curriculum implementation, and group techniques by holding meetings and conducting group discussions.